2018
DOI: 10.1089/scd.2017.0148
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Stem Cell Treatment as a Novel Therapy for Subarachnoid Hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) represents a major health problem in Western society due to high mortality and morbidity, and the relative young age of patients. Currently, efficacious therapeutic options are very limited. Mesenchymal stem cell (MSC) administration has been shown to improve functional outcome and lesion size in experimental models of stroke and neonatal hypoxic-ischemic brain injury. Here, we studied the therapeutic potential of intranasally administered bone marrow-derived MSCs relatively late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Thirty minutes later mice received MSCs applied as 2 doses of 3 µL to each nostril (total volume of 12 µL with 10 6 cells per mouse per day 29 , 30 ) or PBS. We selected this schedule on the basis of our previous work in models of ischemic brain damage 30 33 . Three days before returning to the 5CSRTT training, mice were put back on the food-restriction schedule.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty minutes later mice received MSCs applied as 2 doses of 3 µL to each nostril (total volume of 12 µL with 10 6 cells per mouse per day 29 , 30 ) or PBS. We selected this schedule on the basis of our previous work in models of ischemic brain damage 30 33 . Three days before returning to the 5CSRTT training, mice were put back on the food-restriction schedule.…”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce the adverse reactions, future clinical research should carefully grasp the preoperative indications and try to explore a minimally invasive and effective transplantation method. A large number of animal studies have shown that intranasal delivery is a safe, minimally invasive and effective method for cell transplantation [42][43][44][45]. However, it has not been reported in clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal administration is less invasive than the intracerebral route for the delivery of MSCs to the brain. MSCs migrated from the cribriform plate in the direction of the ipsilateral cerebral lesion site in 2-24 h. Nijboer CH and his teammates showed that intranasal administration of MSCs 6 days after severe SAH enhanced sensorimotor function and decreased the size of the lesion in rats [56]. Furthermore, there was a reduction in neuroinflammation as indicated by astrocyte and microglia/ macrophage activation.…”
Section: Stem Cell Transplantation In Sah and Mechanisms Of Actionmentioning
confidence: 97%